El viajero, la fiebre héctica y las horas. Estudio introductorio de un consilium médico de Mateo Boldieri (s. XV) - Alonso Guardo, Alberto (Anuario de estudios medievales, 2022)
This paper studies a consilium on hectic fever written by Matthew Boldieri, professor of medicine at the University of Padua, originally from Verona, in the fifteenth century. The work explains the treatment that a patient predisposed to this disease should follow during the course of a journey. We analyse the structure and content of the work, investigate the characteristics of the clinical case in the light of the data extracted from the consilium and, finally, examine the schedule used in the regime that the recipient should follow.